Reform and oversight mechanisms are not enough: Access to justice for workers and employment standards in Central Eastern European countries - Karol Muszyński (European Trade Union Institute (ETUI), 2020)
From a strictly formal point of view, employment regulation in Czechia, Hungary, Poland and Slovakia (CEECs) provides an acceptable level of protection for employees. However, workers' formal rights are being violated and circumvented on a massive scale. Because the oversight system is non-effective, employees lack sufficient access to justice; furthermore, the courts and administrative bodies approach regulation in a highly formalised way so that the violations and circumventions become 'normalised' over time, rendering formal regulation ineffective. In many situations, like the use of non-standard forms of employment, adverse interpretations when legal ambiguities arise have been reproduced across CEECs even when formal and targeted regulatory changes have been adopted. The paper argues that, in order to prevent the normalisation of such violations and circumventions, it is necessary to expand access to justice for workers. The paper also puts forward an argument that this could be facilitated where trade unions foster pro-worker legal interpretations by engaging in strategic litigation.
Keywords: 330; Employment law; labor court; labor law; labor union; Eastern Europe; Arbeitsrecht; Arbeitsgericht; Arbeitsrechtsprechung; Gewerkschaft; Osteuropa